PEMANFAATAN BOTOL BEKAS SEBAGAI ALAT FILTER AIR SEDERHANA DAN RAMAH LINGKUNGAN UNTUK DESA LANGKAP KECAMATAN BANGSALSARI KABUPATEN JEMBER - Evi Rohmatul Laili; Rizqy Aiddha Yuniawati; Ayu Balqis Aqilah; Ahmad Luqman Hakim; Nabil Hanaan; Alfi Latifah Nur Azzah; Achmad Reza Saffrialdi; Nafisatul Laeli; Asyifa Hasna; Rosa Devina Paramashinta; Elya Dwi Cania (LPPM Universitas Andalas, 2023)
Water quality is an object that must be considered in accordance with health standards from the Ministry of Health because water quality is a crucial aspect in maintaining health. However, the availability of clean water is often limited, especially in areas with limited access to clean water. The purpose of this community service is to overcome the problem of clean water by using used bottles, sponges, dacron foam, and gravel to create simple water filters. The activities carried out were in the form of outreach about simple filter tools then demonstrations of the use of the tools and distribution of simple filter tools to the residents of Tegalan, Langkap, Jember Regency. The methods used for this simple water filter making activity include socialization, discussion and practice. These three steps were carried out to get maximum results, namely water that became clear after being filtered using a simple water filter. The results of the demonstration using this simple filter tool proved that the water which was originally murky became clear and odorless. This research highlights that simple water filters have potential as a practical solution to improve drinking water quality in resource-constrained areas. The use of this simple water filter can be an initial step that has a positive impact on overcoming difficulties in accessing clean water. It can be concluded that this program brings benefits to all residents of Tegalan, Langkap Village whose water is still murky and dirty because with this simple water filter tool, these people are helped in improving the quality of the water they use on a daily basis.